2004
DOI: 10.2320/matertrans.45.1124
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pore Morphology and Bone Ingrowth on Mechanical Properties of Microporous Titanium as an Orthopaedic Implant Material

Abstract: Successful bone formation which leads to functional osseointegration is determined by the local mechanical environment around boneinterfacing implants. In this work, a novel porous titanium material is developed and tested and then impact of porosity on mechanical properties as a function of bone ingrowth is studied numerically. A superplastic foaming technique is used to produce CP-Ti material with rounded, interconnected pores of 50% porosity; the pore size and morphology is particularly suitable for bone in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 28 publications
2
50
0
1
Order By: Relevance
“…As a consequence, physiological influences of the proximal microporous structure of the prosthesis surface must be considered. Li et al [21] found that the proximal properties of their investigated implant encourage bone ingrowth in the plasma-sprayed layer, which mitigates stress concentration and thus the unloading as well as the overloading ratio of bone tissue. Titanium-coated implants will behave differently when bone ingrowth has taken place, particularly in terms of stress shielding [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, physiological influences of the proximal microporous structure of the prosthesis surface must be considered. Li et al [21] found that the proximal properties of their investigated implant encourage bone ingrowth in the plasma-sprayed layer, which mitigates stress concentration and thus the unloading as well as the overloading ratio of bone tissue. Titanium-coated implants will behave differently when bone ingrowth has taken place, particularly in terms of stress shielding [21].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [21] found that the proximal properties of their investigated implant encourage bone ingrowth in the plasma-sprayed layer, which mitigates stress concentration and thus the unloading as well as the overloading ratio of bone tissue. Titanium-coated implants will behave differently when bone ingrowth has taken place, particularly in terms of stress shielding [21]. Proliferation of bone cells will increase as another consequence of these coating properties [22].…”
Section: Discussionmentioning
confidence: 99%
“…As recently reviewed, [9] routes for creating porous metals in the solid state may take a variety of forms, including gas entrapment, [10][11][12][13][14] fugitive templating, [15][16][17][18][19] powder injection molding, [20][21][22] and powder or hollow sphere sintering. [23][24][25][26][27] Despite the diverse possibilities in solid state foaming, Ni has been primarily produced through vapor-phase deposition on a polymer template, as described by Paserin et al [28][29][30] Developed and sold under the name INCO-FOAM 1 , the process is capable of large-scale output using a reel-to-reel setup that produces metallic foam sheets 1 m wide and 2000 m long.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of metallic materials can be controlled by both alloy design [2][3][4] and the construction of an appropriate structure [5][6][7][8] . A porous implant material with an adequate pore structure showing appropriate mechanical properties, a low Young s modulus, and bone ingrowth has long been sought as the ideal bone substitute 9) .…”
Section: Introductionmentioning
confidence: 99%